Evolution of morphological traits in Verbenaceae - O'Leary, N. (2012)
• Premise of the study: A new infrafamilial circumscription of the Verbenaceae with eight tribes: Casselieae, Citharexyleae, Duranteae, Lantaneae, Neospartoneae, Petreeae, Priveae, and Verbeneae, has been recently proposed, on the basis of molecular phylogenetic studies. Two genera, Dipyrena and Rhaphithamnus, remain unplaced. The aim of this work is to reconstruct the evolutionary history of morphological characters traditionally employed in the classification of the Verbenaceae, with special attention to tribes Verbeneae and Lantaneae. • Methods: Twenty-one characters, related to habit and vegetative morphology, inflorescence and floral morphology, ovary and fruit morphology, as well as chromosome number, were optimized over a molecular phylogeny of Verbenaceae. • Key Results: All tribes are supported by at least one morphological trait except tribes Duranteae and Citharexyleae. Suffrutescent habit, sessile flowers, and four cluses are synapomorphies for tribe Verbeneae. Gynoecium with short style and entire stigma are synapomorphic traits for tribe Lantaneae. Sessile flowers and unicarpellate ovaries are morphological synapomorphies for the new tribe Neospartoneae. Suffrutescent habit is a synapomorphic trait for tribe Priveae. Homothetic pleiobotrya and absence of the adaxial staminode are synapomorphic traits for tribe Casselieae. Undivided fleshy fruits are probably a synapomorphic trait for tribe Petreeae. Putative plesiomorphies for the ancestor of the Verbenaceae are discussed as well as synapomorphic traits within other Verbenaceae clades. • Conclusions: Many of the characters traditionally employed in classification have proven to be very homoplastic, or have been shown not to support relationships within the family. Moreover, traditional assumptions concerning character polarity have in some cases been shown to be incorrect. © 2012 Botanical Society of America.